Same day embolisation followed by microsurgical resection of brain arteriovenous malformations: a single centre early experience. (2nd January 2021) - Brown, Daniel; Graham, Christopher; Smith, Aubrey; Storey, Mathew; Robson, Craig; Maliakal, Paul; Kounin, Gueorgui; Castanho, Pedro
Abstract: Introduction: The purpose of this paper is to report our experience of treating cerebral arteriovenous malformations (AVM) in adults with pre-operative embolisation and microsurgical resection on the same day during a single anaesthetic at a single centre between April 2016 and December 2018. We included both elective AVM and AVM that had bled acutely. Methods: We retrospectively analysed data from patients with cerebral AVMs who underwent embolisation followed by microsurgical resection on the same day at a single neurosurgical centre. Primary endpoints included: Total procedure time (embolisation and microsurgical resection), procedure finish time, intra-operative blood loss, degree of nidus obliteration on postoperative angiography, intensive care unit (ICU) stay, total stay at the neurosurgical centre and modified Rankin Score (pre- and post-procedure). Results: Nineteen patients underwent same-day pre-operative embolisation and microsurgical resection over the 32-month period. The average patient age was 40 years (range 19–66 years). One patient had undergone a prior attempt at embolisation and one patient previously had sterotactic radiosurgery (STRS). Thirteen of the AVM were in the dominant hemisphere and six in the non-dominant hemisphere. Sixteen AVM were located supratentorially and three were in the posterior fossa. Spetzler-Martin grades included 4 grade 1, 10 grade 2, 4 grade 3 and 1 grade 4. The average blood loss intra-operatively was 289 mls. The average list finish time was 19:56 (range 15:10–00:00). Seventeen patients had 100% nidus obliteration on post-operative digital subtraction angiography, one patient had a small remnant and was referred to STRS and one patient died in the ICU post operatively. Conclusion: Overall, the authors believe same-day embolisation and microsurgical resection represents a safe treatment strategy. The technique minimises hemorrhagic complications from delayed venous occlusion and avoids multiple anaesthetics and hospital admissions.